Is There an Optimal Money Supply?: Discussion - Meltzer, Allan H. (Journal of Finance, 1970)
Allan H. Meltzer, Is There an Optimal Money Supply?: Discussion, The Journal of Finance, Vol. 25, No. 2, Papers and Proceedings of the Twenty-Eighth Annual Meeting of the American Finance Association New York, N.Y. December, 28-30, 1969 (May, 1970), pp. 450-453